القول في أركان القراءة والرد على من طعن فيها: Opinion on The Pillars of al-Qira’ah and Arguing Those Who Disagree - Mandakar, Mohammed Falah Ismail (Online Journal of Research in Islamic Studies, 2021)
This research sheds light on the pillars of the proper accurate reading, its concept and the sayings of the people of art thereon, in order to prove the frequency of the ten readings fundamentality and that the difference in the multiplicity of readings is only a significant diversity related to all seven letters. This included presenting what was said regarding the reality of the readings, by an orientalist named (Ignác Goldziher) who was one of the most famous enemies of the Qur’an and its readings by presenting his slander and claims and refuting his saying and suspicion by using a brief scientific style and by depending upon what was said by the specialists in the folds of the books and researches written by them in addition to responding to whatever comes to mind regarding this important matter.